2022
DOI: 10.4018/978-1-7998-7661-8.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Developing Self-Directed Learning Skills for Lifelong Learning

Abstract: This chapter seeks to provide guidance to learners on what may be for many a new perspective on learning that is different from learning styles developed in 13 years of K-12 education. Strategies such as rote memorization and other passive learning techniques may have been sufficient for K-12 classroom learning, but higher education, workplace, and online learning environments require more active and sophisticated learning strategies. It is the perspective of this chapter that the fundamentally different natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These findings are consistent with the research of Downey et al [31], who also concluded that learning through the constructionism approach fosters lifelong learning skills. Hamlin [32] affirmed that active learning, which provides opportunities for students to apply their knowledge and participate in the learning process, is a strategy that promotes SDL skills. These findings are also supported by Tan and Ling [33], who found that SDL skills are developed when students have the freedom to design artifacts, participate in planning their learning journey, and verify and assess their learning.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the research of Downey et al [31], who also concluded that learning through the constructionism approach fosters lifelong learning skills. Hamlin [32] affirmed that active learning, which provides opportunities for students to apply their knowledge and participate in the learning process, is a strategy that promotes SDL skills. These findings are also supported by Tan and Ling [33], who found that SDL skills are developed when students have the freedom to design artifacts, participate in planning their learning journey, and verify and assess their learning.…”
Section: Discussionmentioning
confidence: 99%
“…The society of the future is a competition between people, experience and wisdom (Powell, 2020;Schmidt, 2022). This implies that there is a need for high-level thinkers and lifelong learners with the ability to correlate new and old knowledge, reorganize and process information, analyze problems creatively, solve complex problems effectively, work well in teams to achieve situations in win-win and observe the world critically (Hamlin, 2022;Kroth et al, 2022).…”
Section: Discussionmentioning
confidence: 99%